A microscopic and macroscopic investigation of the adsorption of N719 dye on ZnO nanopowders (ZNP) and ZnO nanorods (ZNR) for dye sensitized solar cells using statistical physics treatment and DFT simulation. Issue 46 (23rd July 2020) - Ben Manaa, Marwa; Issaoui, Noureddine; Al-Ghamdi, Youssef O.; Belmabrouk, Hafedh; Ben Lamine, Abdelmottaleb
Abstract : Adsorption isotherms of N719 dye on (a) ZNP and (b) ZNR and the molecular electrostatic potential (MEP) map of (c) N719 dye and (d) ZnO. Abstract : In this paper, three adsorption isotherms of N719 dye on two different adsorbents, ZnO nanopowder and ZnO nanorods, at three different thicknesses have been fitted using a monolayer model with three types of receptor sites treated by statistical physics. The model involved parameters are: three coefficients ( n 1, n 2 and n 3 ) indicating the numbers of adsorbed dye molecules per site, three parameters ( N m1, N m2 and N m3 ) indicating the receptor site densities and three adsorption energies ((− ε 1 ), (− ε 2 ) and (− ε 3 )). The evolution of these parameters in relation with thickness of ZnO was discussed. The pore size distribution (PSD) of ZnO nanopowder and ZnO nanorods as a function of the thickness has been studied using the chosen adequate model. The molecular electrostatic potential (MEP) has been investigated to optimize the different adsorbed geometries of the complex N719 dye@ZnO. The intermolecular interactions between the N719 dye and the ZnO surface have been studied by using the quantum theory of atoms in molecules (AIM) and reduced density gradient RDG. The results of the MEP, topological AIM and RDG are in agreement with the results of statistical physics